Financial Inclusion, Human Capital, and Wealth Accumulation: Evidence from the Freedman's Savings Bank. (10th February 2020) - Stein, Luke C D; Yannelis, Constantine
Abstract: This paper studies how access to financial services among a previously unbanked group affects human capital, labor market, and wealth outcomes. We use novel data from the Freedman's Savings Bank—created following the American Civil War to serve free Blacks—employing an instrumental variables strategy exploiting the staggered rollout of bank branches. Families with accounts are more likely to have children in school, be literate, work, and have higher occupational income, business ownership, and real estate wealth. Placebo effects are not present using planned but unbuilt branches, or for Whites, suggesting significant positive effects of financial inclusion.